Long-chain polyunsaturated fatty acid biosynthesis in a land-crab with advanced terrestrial adaptations: Molecular cloning and functional characterization of two fatty acyl elongases - Ting, Seng Yeat; Lau, Nyok-Sean; Sam, Ka-Kei; M. Janaranjani; Wong, Swe Cheng; Monroig, Óscar; Quah, Evan Seng Huat; Amirrudin B. Ahmad; Nik Ahmad Irwan Izzauddin Nik Him; Annette Jaya-Ram; Chong, Alexander Shu-Chien (Elsevier, 2022)
Depending on the presence and activities of the front-end fatty acyl desaturases and elongation of very long-chain fatty acid (Elovl) enzymes, animals have different capacities for long-chain (≥C20) polyunsaturated fatty acids (LC-PUFA) biosynthesis. Successful land colonisation in brachyuran crabs requires a shift towards terrestrial food chain with limited LC-PUFA availability. We cloned and functionally characterised two elovl genes from the purple land crab Gecarcoidea lalandii. The two Elovl contained all the necessary motifs of a typical polyunsaturated fatty acids (PUFA) Elovl and phylogenetically clustered in the Elovl1 and Elovl6 clades, respectively. The G. lalandii Elovl1 elongated saturated fatty acids, with low activities towards C20 and C22 PUFA substrates. Moreover, the G. lalandii Elovl6 was particularly active in the elongation of C18 PUFA, although it also recognised monounsaturated fatty acids as substrates for elongation. Collectively, the herein characterised G. lalandii elovl paralogues fulfil all the elongation steps involved in the LC-PUFA biosynthetic pathways. Tissue distribution of the G. lalandii elovl genes, along with the FA composition analyses, suggest the hepatopancreas and gill as key metabolic sites for fatty acid elongation. However, current data suggest that G. lalandii is unable to rely solely on biosynthesis to fulfil LC-PUFA requirements, since front-end desaturase appears to be absent in this species and other decapods.